Total Synthesis of (−)‐Caprazamycin A1. Issue 10 (22nd January 2015) - Nakamura, Hugh; Tsukano, Chihiro; Yasui, Motohiro; Yokouchi, Shinsuke; Igarashi, Masayuki; Takemoto, Yoshiji
Abstract Caprazamycin A has significant antibacterial activity against Mycobacterium tuberculosis (TB). The first total synthesis is herein reported and features a) the scalable preparation of the syn‐β‐hydroxy amino acid with a thiourea‐catalyzed diastereoselective aldol reaction, b) construction of a diazepanone with an unstable fatty‐acid side chain, and c) global deprotection with hydrogenation. This report provides a route for the synthesis of related liponucleoside antibiotics with fatty‐acid side chains.